Determination of the structure of construction technology through the system of organizational and technological parameters of viscose construction. - Ishchenko, О.; Donenko, V.; Ohrimenko, O. (Ways to Improve Construction Efficiency, 2019)
The use of system assessment of technical and economic parameters of technologies for building construction in design and construction practice for choosing resource-saving solutions is expedient and timely. The article deals with the system of organizational and technological parameters of high-rise building, as well as the structure and structure of building technology.